Neglected Cells: Immunomodulatory Roles of CD71+ Erythroid Cells. Issue 3 (March 2019) - Elahi, Shokrollah
Abstract : The main role of red blood cells is oxygen-transportation. However, recent studies have unveiled immunomodulatory functions for their immature counterparts, CD71 + erythroid cells, under different physiological and pathological conditions. Here, I provide a perspective on the recent advances in this field to highlight their importance in health and disease.